2020
DOI: 10.1016/j.jad.2020.07.081
|View full text |Cite
|
Sign up to set email alerts
|

Maternal psychological distress & mental health service use during the COVID-19 pandemic

Abstract: Highlights Maternal depression and anxiety prevalence rates appear elevated during COVID-19. Risk factors for depression and anxiety were evaluated based on child age ranges. Prior psychopathology, poor marital quality, and financial strain affected risk. Mothers primarily obtained mental health information through online resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
356
7
28

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 364 publications
(426 citation statements)
references
References 50 publications
35
356
7
28
Order By: Relevance
“…Specifically, previous studies on Italian women found higher level of anxiety symptoms (Saccone et al, 2020) along with increased concerns and fears about childbirth (Ravaldi et al, 2020) among pregnant women. Moreover, international studies found greater rates of depression, anxiety and stress among mothers of infants and young babies (Cameron et al, 2020). Considering these preliminary results, we can hypothesize that pregnant and postpartum women are at greater risk of developing anxiety, depression, or post-traumatic symptoms.…”
Section: The Current Studymentioning
confidence: 74%
See 1 more Smart Citation
“…Specifically, previous studies on Italian women found higher level of anxiety symptoms (Saccone et al, 2020) along with increased concerns and fears about childbirth (Ravaldi et al, 2020) among pregnant women. Moreover, international studies found greater rates of depression, anxiety and stress among mothers of infants and young babies (Cameron et al, 2020). Considering these preliminary results, we can hypothesize that pregnant and postpartum women are at greater risk of developing anxiety, depression, or post-traumatic symptoms.…”
Section: The Current Studymentioning
confidence: 74%
“…It is within such framework that the association between fathers' commuting to work and mothers' anxiety can be understood: those women whose partners continued working regularly during lockdown showed a greater likelihood of suffering from state anxiety as they could not count on their daily support and they were constantly exposed to the risk of being infected thus adding an element of uncertainty and stress to an, already stressful, situation. In this respect, previous studies have demonstrated that women were extremely worried about themselves, their babies or one of their loved ones being infected with the virus and this resulted in an increased stress and fear (Cameron et al, 2020;Saccone et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Well-established relationships between anxiety and substance use have been identified (Battista, Stewart, & Ham, 2010;Buckner, Heimberg, Ecker, & Vinci, 2013;Burke & Stephens, 1999;Carrigan & Randall, 2003), such that individuals with an anxiety disorder have over a 6-fold increase in reporting drug dependence (Grant et al, 2004). From a public health perspective, it is imperative that we intervene to address maternal anxiety which is elevated during the COVID-19 pandemic (Cameron et al, 2020) to prevent possible increases in maternal substance use. Such interventions may include best-practice psychotherapeutic techniques to treat anxiety disorders, such as cognitive behavioral therapy (Bandelow, Michaelis, & Wedekind, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus (COVID-19) pandemic has resulted in females experiencing over a 2fold increase in stress (Mental Health Commission of Canada, 2020). Females parenting young children further report significantly elevated levels of anxious and depressive symptoms compared to pre-pandemic levels (Cameron et al, 2020). The increase in stress and mental health problems creates concern regarding coping mechanisms.…”
Section: Changes In Maternal Substance Use During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation